2020
DOI: 10.3390/ijerph17103379
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health among Swedish Occupational Therapists: A Cross-Sectional Study

Abstract: The Swedish public sector is facing great challenges in recruiting and retaining healthcare professionals, due to increasing sick leave numbers. The aim of this study was to describe Swedish occupational therapists’ occupational health in terms of risk factors in the social and organizational work environment, occupational balance, and work-related mental health problems. A web survey was emailed to all working members of the Swedish Association of Occupational Therapists (n = 7600) and 3658 answered the surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
1
20
1
Order By: Relevance
“…This is in keeping with a study by Bruschini, Carli and Burla, who found that 32% of the paramedical staff (n ¼ 391) (occupational therapists, speech therapists and physiotherapists) showed signs of mental health problems such as emotional exhaustion and 14% were at high risk of burnout [18]. In a newly conducted study by Lex en and colleagues [1] of 3,658 Swedish occupational therapists, the participating occupational therapists generally rated their workload as heavy, with increased stress as a consequence. In the study, almost a fifth of the participating occupational therapists reported work-related mental health problems in the form of symptoms of mild incipient exhaustion or pronounced exhaustion disorder.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in keeping with a study by Bruschini, Carli and Burla, who found that 32% of the paramedical staff (n ¼ 391) (occupational therapists, speech therapists and physiotherapists) showed signs of mental health problems such as emotional exhaustion and 14% were at high risk of burnout [18]. In a newly conducted study by Lex en and colleagues [1] of 3,658 Swedish occupational therapists, the participating occupational therapists generally rated their workload as heavy, with increased stress as a consequence. In the study, almost a fifth of the participating occupational therapists reported work-related mental health problems in the form of symptoms of mild incipient exhaustion or pronounced exhaustion disorder.…”
Section: Introductionsupporting
confidence: 86%
“…In recent years, in Sweden as in other European countries, there has been an increase in sick leave for mental health problems resulting from increased job strain [1,2]. People spend a large proportion of their waking life at work, and so the work environment has a major role in well-being and health [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prevalence rates of signs of exhaustion in LUCIE were also higher among the principals when compared with a Swedish occupational sample consisting of 3658 occupational therapists (94% females) [62].…”
Section: Discussionmentioning
confidence: 81%
“…In this organisation sample, the occurrence of stress and exhaustion warnings in LUCIE were 8 and 5.5%, respectively [ 61 ]. In addition, the prevalence rates of signs of exhaustion in LUCIE were also higher among the principals when compared with a Swedish occupational sample consisting of 3658 occupational therapists (94% females) [ 62 ]. In this sample of occupational therapists, the occurrence of stress and exhaustion warnings in LUCIE were 11 and 7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The questions in QPSmismatch have been grouped according to Maslach and Leiter's model of burnout development [21] into the following groups or dimensions: 1) Workload, 2) Control, 3) Community, 4) Reward, 5) Justice and 6) Values. QPS-mismatch has five response alternatives ranging from very seldom or never (1) to very often or always (5). The reliability was shown to be good (Cronbach alpha 0.72-0.90 in all dimensions) [Österberg, 2016, [19].…”
Section: Data Collectionmentioning
confidence: 99%